CUIDADO À PARTURIENTE NO CONTEXTO DO NASCIMENTO: PROPOSTA DE UM PROTOCOLO DE PARTICIPAÇÃO DO ACOMPANHANTE - Araújo, Caroline Pacheco (2019)
of women at the time of delivery, the qualification of assistance based on scientific evidence and the reduction of maternal and child morbidity and mortality. The companion of choice of the parturient plays an essential role in this context, being inserted in the good practices of attention to the childbirth and birth and helping so that the woman becomes protagonist of the process of gestar and to give birth in a positive form. General Objective: Elaborate a proposal of protocol of participation of the companion in order to provide comfort in the context of the birth and guide the assistance to the woman, baby and family. Specific Objectives: To analyze the scientific productions on the participation of the companion in the birth; To discuss with the multiprofessional team at the Obstetric Center of the University Hospital of Santa Maria (HUSM) about the importance of the participation of the companion in the context of the birth, based on the physical, environmental and social contexts that involve the Comfort Theory; Elaborate a flowchart of mobility of the companion of the parturients and puerperas hospitalized in the (HUSM); Elaborate a POP - standard operating procedure for accompanying orientations in the context of birth; Creation and implementation of a "Gestando Saberes" study group in the CO. Theoretical reference: the research was based on the Theory of Comfort and NANDA II. Methods: The methodology used was action research. He used the focal group as data collection technique. The setting was the HUSM Obstetric Center. Participated in the research health professionals of the multiprofessional team acting at the Obstetric Center. The Thematic Content Analysis, proposed by Minayo, was used to analyze the data. Results: The study allowed the re-signification and reflection of a multiprofessional team about the participation of the accompanying person at birth and the elaboration of an instrument in the format of protocol to guide and organize the professionals' action in front of the change of the attention model promoting the good practices of obstetric care, dialogue between the various health areas and care centered on women, newborns and the family. Final Product: Protocol of participation of the companion in the context of the birth. Flowchart of mobility of the companion of the parturient hospitalized in HUSM. Elaboration of a POP - standard operating procedure for accompanying orientations in the context of birth. Creation and implementation of a study group, called "Gestando Saberes", in the CO. Final considerations: Among the good practices in the attention to humanized childbirth the presence of the companion or some person who is significant is strongly included. It is necessary to transcend barriers, be they institutional, personal and outdated delivery models. Bringing value and meaning to the moment of the woman, newborn, and family will only be possible by transforming the existing pattern of obstetric attention. Therefore, processes of attention to childbirth require a new form of management and care, enabling dialogue and the active participation of all those involved in the birth process.